Diagnosis Kesulitan Belajar Matematika Siswa Ditinjau Dari Kemampuan Koneksi Matematika Siswa Kelas VIII SMP Muhammadiyah 2 Kartasura Tahun Ajaran 2016/2017 - Sari, Anita Wulan, Dr. Sumardi, M.Si (2017)
ABSTACT Anita Wulan Sari / A410130187. DIAGNOSIS OF STUDENT LEARNING DIFFICULTIES IN MATHEMATICS CONNECTION BASED ON MATH SKILLS STUDENTS (In class VIII SMP Muhammadiyah 2 Kartasura Academic Year 2016/2017). Essay. The Faculty of Education, University of Muhammadiyah Surakarta, April 2017. Mathematics is a science that is interrelated and not a science dealing with collection of the separated material. Students think math has a high degree of difficulty. The purpose of this study was to describe the mathematics learning difficulties experienced by students if the terms of the ability to connect math grade students of SMP Muhammadiyah 2 Kartasura Academic Year 2016/1017. Qualitative descriptive research, with research subjects are students of class VII SMP Muhammadiyah 2 Kartasura. Data collection techniques using observation, testing and interview. Data analysis technique is done by means of data collection, data reduction, presentation (display) of data and conclusion. Conclusions This study is the difficulty of learning mathematics learners in terms of the mathematical connection capabilities: lack of facilities and infrastructures of learning, less well understood mathematical concepts previously learned, do not associate a mathematical concept known before the concept to be learned, the habit of learning not with understanding the concept but from the sample questions provided by the teacher or textbook, consider mathematics as a science that between one and other concepts are mutually exclusive, lack of motivation within themselves to learn about a particular subject matter in both mathematics and other disciplines, less aware of the benefits of the concept in mathematics to support and enhance its capabilities in other fields. Keywords: learning, the ability, math connections, learning difficulties